SCMA System Design With Index Modulation via Codebook Assignment - Tekce, Ferdi; Ayten, Umut Engin; Durak-Ata, Lutfiye (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2021)
Sparse code multiple access (SCMA) is a promising non-orthogonal multiple access (NOMA) scheme for massive machine-type communications for 5G-and-beyond communication systems. Innovative use of orthogonal frequency division multiplexing with index modulation (OFDM-IM) takes advantage of using tone indices in data transmission. In this study, we propose a novel multiplexing and multiple access scheme, namely SCMA based on OFDM-IM (SCMA-IM). SCMA-IM method can be implemented in uplink NOMA systems in an efficient way with similar computational complexity as SCMA. In this method constellation differences and diversity are obtained via SCMA codebooks (CBs) and the employment of CBs is transferred to index modulation (IM). Performance improvement is achieved via CBs so that the number of data bits carried by indices increases more than one bit with different constellations, and also with the number of CBs assigned. In order to determine the indices used in IM, the receiver structure is simplified by the message passing algorithm and log-likelihood ratio detection process used in SCMA receivers without indexing the receiver. Thus, a new NOMA scheme is obtained by coding with IM. Bit error rate performance of the system is studied for 150% and 200% overloading factors.
Keywords: NOMA; OFDM; Bit error rate; Modulation; Receivers; Throughput; Encoding; Orthogonal frequency division multiplexing with index modulation (OFDM-IM); sparse code multiple access (SCMA); non-orthogonal multiple access (NOMA); message passing algorithm (MPA); log-likelihood ratio (LLR); MULTIPLE-ACCESS; DETECTOR; Engineering; Telecommunications; Transportation